2019
DOI: 10.7324/japs.2019.90314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synergism between Cefotaxime and Allium sativum against Extended-spectrum beta-lactamase and Ambler class C co-producers

Abstract: The present study evaluates the synergistic association between Cefotaxime and aqueous garlic (Allium sativum) extract (AGE) on extended spectrum beta-lactamase (ESBL) and Ambler Class C (AmpC) co-producing Escherichia coli strains from skin and soft tissue infections (SSTIs). Ceftazidime-resistant E. coli strains were screened for betalactamase production by phenotypic confirmatory disc diffusion test (PCDDT) and E-test. Antibacterial activity of AGE was examined by the disc diffusion method and the minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
2
1
Order By: Relevance
“…Even though the synergism detected using checkerboard method was not established by the time kill curve in this study, the lack of antagonistic effect as shown in the E. hirta whole plant acetone extract and honey mixture is an inspiring outcome which suggests that purified acetone extracts and honey has potential to be effective as combination or mono therapy, also they may contain a myriad of bioactive constituents that can enhance the activity of ciprofloxacin against drug resistant bacteria isolates associated with OM. We combined E. hirta whole plant acetone extract, honey and ciprofloxacin in this study to treat the MDR test isolates, the treatment's time kill assay showed bactericidal activity against P. mirabilis isolate after 24 h. This is analogous with report by Abegunde et al (2018) and Shah & Williamson (2019), in Nigeria and India respectively. This bactericidal action recorded in this study shows E. hirta acetone extract,…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 588supporting
confidence: 84%
See 4 more Smart Citations
“…Even though the synergism detected using checkerboard method was not established by the time kill curve in this study, the lack of antagonistic effect as shown in the E. hirta whole plant acetone extract and honey mixture is an inspiring outcome which suggests that purified acetone extracts and honey has potential to be effective as combination or mono therapy, also they may contain a myriad of bioactive constituents that can enhance the activity of ciprofloxacin against drug resistant bacteria isolates associated with OM. We combined E. hirta whole plant acetone extract, honey and ciprofloxacin in this study to treat the MDR test isolates, the treatment's time kill assay showed bactericidal activity against P. mirabilis isolate after 24 h. This is analogous with report by Abegunde et al (2018) and Shah & Williamson (2019), in Nigeria and India respectively. This bactericidal action recorded in this study shows E. hirta acetone extract,…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 588supporting
confidence: 84%
“…This study also revealed low fractional inhibitory concentration index value on P. mirablis (0.02) when E. hirta whole plant acetone extract and honey was mixed with ciprofloxacin. This correlate with Shah and Williamson (2019) who showed low fractional inhibitory index value when aqueous garlic extract was combined with antibiotics against resistant strain of E. coli in India. The synergistic effects of E. hirta whole plant acetone extract, honey and ciprofloxacin shown in this study reveals high level of ciprofloxacin potentiation against multidrug resistant P. mirablis isolate.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas / 588supporting
confidence: 74%
See 3 more Smart Citations